PTH-086 Surgery for perianal crohn's disease: uk national population based cohort study. (22nd June 2015) - Chhaya, V; Saxena, S; Cecil, E; Curcin, V; Subramanian, V; Majeed, A; Pollok, R
Abstract : Introduction: Recent falls in surgical intervention in Crohn's disease (CD) are associated with improvements in drug therapy. However, little is known about the changing incidence of perianal manifestations, which can be debilitating and may lead to perianal surgery including proctectomy. Our aim was to determine trends in perianal surgery rates using the Clinical Practice Research Datalink (CPRD) and their relation to the diagnosis of CD. Method: Incident cases of CD were identified between 1989–2009 from the nationally representative CPRD which contains clinical records and prescribing data for 13 million people in the UK and is a validated research database. Patients were included if they had been registered with a practice for greater than 12 months. The primary outcome was first perianal surgery defined by READ/OXMIS coding. We used Kaplan-Meier survival analysis to demonstrate the rate of first perianal surgery at 1, 5, 10 and 20 years after diagnosis. We also determined the time to first perianal surgery relative to the date of diagnosis. Results: The CPRD contained 9391 incident cases of CD between 1989–2009. 405 patients underwent perianal surgery of whom 75% (305) had a single surgery, 16% (63) required 2 surgeries, 6% (26) required 3 surgeries and 3% (11) required 4 or more surgeries during follow up. The commonest forms of perianal surgery were abscess drainage (51%), laying open of fistula (20%) and proctectomy (11%). The overall rate of perianal surgery was 2.6% (95% CI: 2.3–2.9%), 4.0% (95% CI: 3.6–4.4%), 5.5% (95% CI: 4.9–6.2%) and 8.4% (95% CI: 7.0–9.9%) at 1, 5, 10 and 20 years after diagnosis. The median time to perianal surgery was 4 months (IQR: –1.3–2.7 years) after diagnosis. Of all the patients undergoing perianal surgery, 13% (n = 53), 17% (n = 69) and 34% (n = 137) had surgery within 6 months, 1 year and 5 years, respectively before receiving a formal CD diagnosis. 59% (n = 238) of all patients undergoing perianal surgery had this performed before the first anniversary of their CD diagnosis. Conclusion: This is the first study to evaluate a nationally representative population and shows that the majority of patients undergoing perianal surgery are operated on within the first year of CD diagnosis. A third of patients who had perianal surgery underwent the procedure in the 5 years preceding the diagnosis of CD. Surgical treatment for perianal disease should alert clinicians to the possible underlying diagnosis of CD. Disclosure of interest: None Declared.